Predictors of short-term successful discontinuation of continuous renal replacement therapy: results from a prospective multicentre study - Stads, Susanne (BMC Nephrol, 2019)
BACKGROUND: Prediction of successful discontinuation of continuous renal replacement therapy (CRRT) might reduce complications of over- and under-treatment. The aim of this study was to identify renal and non-renal predictors of short-term successful discontinuation of CRRT in patients in whom CRRT was stopped because renal recovery was expected and who were still in the Intensive Care Unit (ICU) at day 2 after stop CRRT. METHODS: Prospective multicentre observational study in 92 patients alive after discontinuation of CRRT for acute kidney injury (AKI), still in the ICU and free from renal replacement therapy (RRT) at day 2 after discontinuation. Successful discontinuation was defined as alive and free from RRT at day 7 after stop CRRT. Urinary neutrophil gelatinase-associated lipocalin (NGAL) and clinical variables were collected. Logistic regression and Receiver Operator Characteristic (ROC) curve analysis were performed to determine the best predictive and discriminative variables. RESULTS: Discontinuation of CRRT was successful in 61/92 patients (66%). Patients with successful discontinuation of CRRT had higher day 2 urine output, better renal function indicated by higher creatinine clearance (6-h) or lower creatinine ratio (day 2/day 0), less often vasopressors, lower urinary NGAL, shorter duration of CRRT and lower cumulative fluid balance (day 0–2). In multivariate analysis renal function determined by creatinine clearance (Odds Ratio (OR) 1.066, 95% confidence interval (CI) 1.022–1.111, p = 0.003) or by creatinine ratio (day 2/day 0) (OR 0.149, 95% CI 0.037–0.583, p = 0.006) and non-renal sequential organ failure assessment (SOFA) score (OR 0.822, 95% CI 0.678–0.996, p = 0.045) were independently associated with successful discontinuation of CRRT. The area under the curve of creatinine clearance to predict successful discontinuation was 0.791, optimal cut-off of 11 ml/min (95% CI 6–16 ml/min) and of creatinine ratio 0.819 (95% CI 0.732–0.907) optimal cut-off of 1.41 (95% CI 1.27–1.59). CONCLUSION: In this prospective multicentre study we found higher creatinine clearance or lower creatinine ratio as best predictors of short-term successful discontinuation of CRRT, with a creatinine ratio of 1.41 (95% CI 1.27–1.59) as optimal cut-off. This study provides a practical bedside tool for clinical decision making.